Drug Manufacturing and Access to Medicine in Nepal – A Literature Review of Challenges and Proposed Remediation - Bhatt, Hemant; Santosh, KC; Thapa, Panna (Dhaka University Journal of Pharmaceutical Sciences, 2022)
In recent years considerable attention has been paid to the issue of access to medicine. Access to medicine cannot depend on the decision of private industries only but also on government policies and strategies. According to National Health Policy2019, it is the right of all citizens to have basic health care service including access to safe, efficacious and quality medicine. Nepal is a landlocked country in South Asia. Nepal is a diverse country with a varied culture, language, and biodiversity, but generally affected by the common disease (e.g. tuberculosis, COPD, diarrhoeal disease, diabetes and malaria). There are 65 plus private pharmaceutical industries in operation in Nepal and approximately 60% of drugs are imported from India and third-world countries. The only government owned pharmaceutical industry is ‘Nepal Aushadhi Limited’ which is not fully operational in manufacturing essential medicine. Private manufacturers focus mainly on brand competition for private consumption but not in essential medicines. Some essential medicines are totally imported from India and other countries (e.g. insulin). The Nepal government has Free Drug List (FDL) consisting 70 medicines that should be provided free to the all patients but these are not accessible to all citizen of rural areas due to poor logistic management, supply chain and transportation facilities. Quality and adequacy of health services and medicines are the main problem in rural areas. This article mainly focuses on challenges of drug manufacturing and access to safe, efficacious and quality medicines in Nepal. It also emphasizes on strategies and policies being implemented to solve these problems. It is obvious that solving the challenges to provide safe, efficacious and quality medicine is collective responsibility of government of Nepal, private manufacturing industries, regulatory bodies, health professional, the patient and NGO, INGOs working on healthcare system of Nepal. Dhaka Univ. J. Pharm. Sci. 20(3): 373-379, 2022 (June) Centennial Special Issue